PINK1 regulates mitochondrial fission/fusion and neuroinflammation in β-amyloid-induced Alzheimer's disease models. (March 2022) - Wang, Xiaojuan; Xue, Yongqiang; Yao, Yang; Li, Yang; Ji, Xuefei; Chi, Tianyan; Liu, Peng; Zou, Libo
Abstract: Disrupted mitochondrial fission/fusion balance is consistently involved in neurodegenerative diseases, including Alzheimer's disease. PTEN-induced putative kinase 1 (PINK1), a mitochondrial kinase, has been reported to prevent mitochondrial injury, oxidative stress, apoptosis, and inflammation. However, to the best of our knowledge, the contribution of PINK1 to Aβ-induced mitochondrial fission/fusion has not been reported. In the present study, we showed that PINK1 deficiency promoted mitochondrial fission and fusion, aggravated mitochondrial dysfunction, and promoted neuroinflammatory cytokine factor production induced by intracerebroventricular (ICV) injection of Aβ25-35 in rats. In vitro experiments have also showed that Aβ25-35 caused more severe cell injury in PINK1-knockdown PC12 cells. These cells suffered more extensive death when exposed to proinflammatory cytokines. Lastly, we found that PINK1 overexpression significantly inhibited mitochondrial fusion, improved mitochondrial dysfunction, and reduced neuroinflammatory cytokine production induced by Aβ25-35 . The current study suggests the involvement of PINK1 in Aβ25-35 -mediated mitochondrial dynamics and that PINK1 may be a potential target for therapies aimed at enhancing neuroprotection to ameliorate Aβ25-35 -induced insults. Highlights: PINK1 deficiency promotes ICV-Aβ induced mitochondrial fission and fusion. PINK1 deficiency aggravates Aβ induced neuroinflammatory cytokine factor production. PINK1 overexpression inhibits ICV-Aβ induced mitochondrial fusion. PINK1 overexpression reduces Aβ induced neuroinflammatory cytokines.